2018
DOI: 10.1016/j.bbabio.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Probing the local lipid environment of the cytochrome bc1 and Synechocystis sp. PCC 6803 cytochrome b6f complexes with styrene maleic acid

Abstract: Intracytoplasmic vesicles (chromatophores) in the photosynthetic bacterium Rhodobacter sphaeroides represent a minimal structural and functional unit for absorbing photons and utilising their energy for the generation of ATP. The cytochrome bc1 complex (cytbc1) is one of the four major components of the chromatophore alongside the reaction centre-light harvesting 1-PufX core complex (RC-LH1-PufX), the light-harvesting 2 complex (LH2), and ATP synthase. Although the membrane organisation of these complexes is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Cytbc1 SMALPs and Rba. sphaeroides chromatophores were prepared and analyzed by thin layer chromatography (TLC) and phosphate quantification as previously described (Swainsbury et al, 2018), with the exception that lipid band intensities were plotted as a fraction of the total.…”
Section: Methodsmentioning
confidence: 99%
“…Cytbc1 SMALPs and Rba. sphaeroides chromatophores were prepared and analyzed by thin layer chromatography (TLC) and phosphate quantification as previously described (Swainsbury et al, 2018), with the exception that lipid band intensities were plotted as a fraction of the total.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids have been detected in SMALPs in several studies and lipid preferences for many proteins have been characterised for the first time using SMALPs [32,33]. A study of Rhodobacter sphaeroides proteins solubilised by SMA showed that they retained significant numbers of lipids [34]. However, they also related the solubilisation efficiency of R. sphaeroides MPs to their local lipid environment.…”
Section: Latest Applications Of Smalpsmentioning
confidence: 99%
“…Light is absorbed by either the LH2 or LH1 antenna, arranged in protein-rich arrays, and excitation energy is transferred within picoseconds to the RC, where charge separation drives the reduction of quinone to quinol and the oxidation of cytochrome c 2 [ [5] , [6] , [7] , [8] , [9] , [10] ] . These products are utilised by the cytochrome bc 1 complex, which resides in a locally lipid-rich region, to re-reduce oxidised cytochrome c 2 and oxidise quinol to quinone [ 3 , 4 , 11 , 12 ]. This cyclic process results in the transport of protons into the lumen (periplasm) of the chromatophore, which drive ATP generation by ATP synthase [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%